How do I derive Kepler's 3rd law using Newton's Law of gravitation, in the case of a circular orbit?

Kepler's 3rd law states that the cube of the radius, r from a planet is directly proportional to the square of the orbital period around it, T: r3 ∝ T2 (this is the result we want!)
We know Newton's Law of gravitiation: Fg = GMm/r2 We also know the equations of circular motion, and that Fc = mv2/r The key is that in a circular orbit, the centripetal force Fc is provided by the gravitational force FgSo we can equate Fc = Fg=> mv2/r = GMm/r2 We can see m cancels on both sides:v2/r = GM/r2 Remember in circular motion v depends on r and T:v = ω r and ω = 2π/T so v = 2πr/Tsubstituting v = 2πr/T back into equation 1:4π2r/T2 = GM/r2Note how m cancels out and v is substituted with r and T terms: so the mass/velocity of the satellite don't matter, and the result is general for ANY orbiting body!Rearrange so the constants are on one side, and r and T terms on the other:r3/T2 = GM/4π2or, r3 = k T2 where the constant k = GM/4π2
=> r3 ∝ T2 for any planet ...Kepler's 3rd law!

Answered by Greta C. Physics tutor

4997 Views

See similar Physics A Level tutors

Related Physics A Level answers

All answers ▸

Describe and explain the photoelectric effect in terms of photons interacting with the surface of a metal.


A ball is fired at an angle of 50 degrees with a velocity of 10 ms^-1, at what time does it first hit the floor?


Describe how a capacitor works.


The tip of each prong of a tuning fork emitting a note of 320Hz vibrates in SHM with an amplitude of 0.50mm. What is the speed of each tip when its displacement is zero?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences